Factors Influencing Functional Heterogeneity in Human Mucosa-Associated Invariant T Cells - Dias, Joana; Boulouis, Caroline; Sobkowiak, Michał J.; Lal, Kerri G.; Emgård, Johanna; Buggert, Marcus; Parrot, Tiphaine; Gorin, Jean-Baptiste; Leeansyah, Edwin; Sandberg, Johan K. (Frontiers in Immunology, 2018)
Mucosa-associated invariant T (MAIT) cells are unconventional innate-like T cells that recognize microbial riboflavin metabolites presented by the monomorphic MR1 molecule. Despite the high level of evolutionary conservation of MR1 and the limited diversity of known antigens, human MAIT cells and their responses may not be as homogeneous as previously thought. Here, we review recent findings indicating that MAIT cells display microbe-specific response patterns with multiple layers of heterogeneity. The NK cell receptor CD56 marks a MAIT cell subset with distinct response profile, and the TCR β-chain diversity influences responsiveness at the single cell level. The MAIT cell tissue localization also influences their response profiles with higher IL-17 in tissue-resident MAIT cells. Furthermore, there is emerging evidence that the type of antigen presenting cells, and innate cytokines produced by such cells, influence the quality of the ensuing MAIT cell response. On the microbial side, the expression patterns of MR1-presented antigenic and non-antigenic compounds, expression of other bioactive microbial products, and of innate pattern recognition ligands all influence downstream MAIT cell responses. These recent findings deepen our understanding of MAIT cell functional diversity and adaptation to the type and location of microbial challenge.